Ayurveda Management Of Scleroderma Through Samshamana & Shodhana Therapy - A Case Study - Pinkee, Km; Chowdhury, Nur Mohammad Iqbal; Joshi, Ram Kishor (International Research Journal of Ayurveda & Yoga, 2024)
Scleroderma or morphea is a rare fibrosing disorder restricted to the skin, subcutaneous tissue, bone and occasionally the underlying central nervous system. Scleroderma is of two type- Generalized and Systemic in which Systemic sclerosis is a connective tissue disease of unknown etiology involving many systems and is characterized by autoimmunity, inflammation, vasculopathy, and progressive interstitial and vascular fibrosis in the skin and internal organs. According to Ayurveda point of view it is Vata and Rakta predominant disorder and called morphea. So we treat through vata and morphea medications with the help of Samshamana and Shodhana therapy.